O computador na escola: contextualizando a formação de professores - praticar e teoria, refletir a prática - Almeida, Maria Elizabeth Bianconcini Trindade Morato Pinto de (2000)
The present study aims at understanding teachers' development towards the incorporation of the computer in their pedagogical practice and the consequences of its use, searching for signs of possible transformations in the teachers' practice and their influence in the school. For this, I analyse teachers' development towards the educational use of the computer, carried out by the sub-project Computer Tools in Education at the PECjPUC-SP, run by the Programa de Educação Continuada da Secretaria do Estado (Continuous Education Programme of the State Secretary), for which PUCjSP worked together with the schools in Pólo 4. As a contribution to this area of investigation I identified categories of analysis, within the theoretical basis used for the experience, from which I looked for hints that indicated changes in the teachers' practice. I have also brought an analysis of improvements, potentialities, challenges, difficulties, incoherence and ambiguities on teachers' development that might be a reference for other activities, supplying elements for the recontextualization of teacher development programmes focused on incorporating the computer into their pedagogical practice. Due to the particular features of a large-scale development programme that is embedded in a public education system, three schools were selected to be studied in depth. I presented a general overview of the situation not only based on objective facts, but mainly on impressions, perceptions and feelings brought about by the teachers, students, and heads, as well as by the two kinds of developers (instructors and tutors). I used a multidimensional data-analysis software to establish the relation among data, theory and practice, allowing for an enlargement of the view, observation, perception and interpretation scopes, re-contextualizing practice and theory. Results have shown the analysed categories and their related themes were present in the subjects' reports when the programme enabled them to develop autonomy to: learn how to learn to work out problems they come across in life and in their profession; learn how to think and make decisions; be open to the new, the unknown and the unpredictable; use the computer for the search, selection and exchange of information and experiences, and for the continuous reconstruction of knowledge, reflection, interaction and cooperation. However, it has been noticed the required autonomy for self-development related to innovative actions towards the computer will not exist without the educational managers' support and the community's participation, involving the school actors and surroundings, which necessarily asks for a change in the school structure